(untitled) (Research, Society and Development, 2020)
Objective: to establish the meaning of teaching-service integration and identify the potentializing actions for or development of the teaching-service integration from the perspective of residents linked to a multiprofessional Residency Program in Health. Method: appreciative research, carried out with seven residents linked to a multiprofessional Residency Program in Health in southern Brazil. A data production was carried out with interviews and discussion groups, by means of the DSPD Cycle, corresponding to the stages: Discovery, Dream, Design and Destiny, in the period from 2018 to 2019, after approval in the ethics committee. The results are submerged in a content analysis. Results: the teaching-service integration involves meanings such as affection and desire to be as an other and to be present and can be potentiated by means of non-program institutes, offered in powerful spaces, such as: tutorials, tutorials, theoretical classrooms, expanded tutorials, show of practices, health education actions, permanent health education and assemblies between residents. Conclusion: the residents will observe that there are powerful and strategic practices in the residency programs in health that can facilitate and mediate relations and dialogue in the qualification of assisting users according to the principles of the Unified Health System.